Soncino - Gesellschaft der Freunde des jüdischen Buches Ein Beitrag zur Kulturgeschichte - Bürger, Karin; Sonder, Ines (Europäisch-jüdische Studien - Beiträge, 2014)
In May 1924, the Soncino Society of the Friends of the Jewish Book was founded in Berlin. Named after the Soncinos, a 15th to 16th century Jewish-Italian family of printers, it was the first society of Jewish bibliophiles, and set the goal of publishing rare Jewish books and Hebrew printings. The eight essays in this volume explore the history of the Society and its commitment to Hebrew book culture.